Glyphosate-based herbicides modulate oxidative stress response in the nematode Caenorhabditis elegans - Kronberg, Maria Florencia (2018)
Glyphosate-based formulation is used as non-selective and post-emergent herbicides in urban and rural activities. In view of its recurring applications in agricultural producing countries, the increase of glyphosate concentration in the environment stresses the need to test the adverse effects on non-target organisms and assess the risk of its use. This paper analyzes the toxicological and oxidative stress and modulatory effects of a glyphosate commercial formulation (glyphosate F) on the nematode Caenorhabditis elegans. We detected ROS production and enhancement of oxidative stress response in glyphosate F-treated nematodes. Particularly, we found an increased ctl-1 catalase gene expression of a catalase specific activity. In addition, we showed that glyphosate F treatment activated the FOXO transcription factor DAF-16, a critical target of the insulin/IGF-1 signaling pathway, which modulates the transcription of a broad range of genes involved in stress resistance, reproductive development, dauer formation, and longevity. In summary, the exposure of glyphosate F induces an oxidative imbalance in C. elegans that leads to the DAF-16 activation and consequently to the expression of genes that boost the antioxidant defense system. In this regard, clt-1 gene and catalase activity proved to be excellent biomarkers to develop more sensitive protocols to assess the environmental risk of glyphosate use.